The kindergarten educators' attitudes towards caring of environment (A field study on a sample of kindergarten educators in Lattakia) - Ghanem , Thanaa; Shribah , Bushra; Arrage , Abeer (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research aims at determine the kindergarten educators' attitudes towards caring of environment in the following fields: (consumption rationing, cleaning, caring of plants and animals, environmental pollution, riddance of wastes), to achieve that, a questionnaire was applied on a random sample of (90) kindergarten educators in Lattakia, and relying on appropriate statistical methods, results were as following: 1. The kindergarten educators' attitudes towards caring of environment were a high. 2. The kindergarten educators' attitudes towards caring of environment were a high in the field of riddance of wastes, environmental pollution, cleaning, and caring of plants and animals. 3. The kindergarten educators' attitudes towards caring of environment were a medium in the field of consumption rationing. 4. The kindergarten educators' attitudes towards the environment are better in city kindergarten, and according to their scientific qualification.